The Development of Islamic Crowdfunding in Indonesia and Its Impact towards SMEs - Rifka Mustafida; Najim Nur Fauziah; Zahra Nabila Kurnia (Hasanuddin Economics and Business Review, 2021)
Small and Medium Enterprises (SMEs) is taking role as the backbone for sustained economic growth, particularly in developing countries. However, SMEs might not easily get the financing from the banking institution due to the lack of financial history and collateral. Islamic crowdfunding has become a solution to deliver accessible financial services to the unbanked SMEs in the countries, especially in Indonesia.Â Islamic crowdfunding impacts the SMEs in regard to the ease of obtaining capital access, improving the welfare of SMEs, and creating growth for the national economy in the long-term. By using literature review, this study aims to show how the Islamic crowdfunding develops and how it affects the SMEs in Indonesia. The result shows that Islamic crowdfunding potentially benefits the SMEs in capital access, improving the welfare and economic growth.Â Â